Peer observation of teaching as a faculty development tool - Sullivan Peter B (BMC Medical Education, 2012)
Abstract Background Peer observation of Teaching involves observers providing descriptive feedback to their peers on learning and teaching practice as a means to improve quality of teaching. This study employed and assessed peer observation as a constructive, developmental process for members of a Pediatric Teaching Faculty. Methods This study describes how peer observation was implemented as part of a teaching faculty development program and how it was perceived by teachers. The PoT process was divided into 4 stages: pre-observation meeting, observation, post-observation feedback and reflection. Particular care was taken to ensure that teachers understood that the observation and feedback was a developmental and not an evaluative process. Twenty teachers had their teaching peer observed by trained Faculty members and gave an e-mail ‘sound-bite’ of their perceptions of the process. Teaching activities included lectures, problem-based learning, small group teaching, case-based teaching and ward-based teaching sessions. Results Teachers were given detailed verbal and written feedback based on the observer’s and students’ observations. Teachers’ perceptions were that PoT was useful and relevant to their teaching practice. Teachers valued receiving feedback and viewed PoT as an opportunity for insight and reflection. The process of PoT was viewed as non-threatening and teachers thought that PoT enhanced the quality of their teaching, promoted professional development and was critical for Faculty development. Conclusions This study demonstrated that PoT can be used in a constructive way to improve course content and delivery, to support and encourage medical teachers, and to reinforce good teaching.